Economic and Environmental Assessment of Seed and Rhizome Propagated Miscanthus in the UK - Hastings, Astley; Mos, Michal; Yesufu, Jalil A.; McCalmont, Jon; Schwarz, Kai; Shafei, Reza; Ashman, Chris; Nunn, Chris; Schuele, Heinrich; Cosentino, Salvatore; Scalici, Giovanni; Scordia, Danilo; et al. (Frontiers in Plant Science, 2017)
Growth in planted areas of Miscanthus for biomass in Europe has stagnated since 2010 due to technical challenges, economic barriers and environmental concerns. These limitations need to be overcome before biomass production from Miscanthus can expand to several million hectares. In this paper we consider the economic and environmental effects of introducing seed based hybrids as an alternative to clonal M. x giganteus (Mxg). The impact of seed based propagation and novel agronomy was compared with current Mxg cultivation and used in ten commercially relevant, field scale experiments planted between 2012 and 2014 in the UK, Germany and Ukraine. Economic and greenhouse gas (GHG) emissions costs were quantified for the following production chain: propagation, establishment, harvest, transportation, storage and fuel preparation (excluding soil carbon changes). The production and utilisation efficiency of seed and rhizome propagation were compared. Results show that new hybrid seed propagation significantly reduces establishment cost to below £900 ha-1. Calculated GHG emission costs for the seeds established via plugs, though relatively small, was higher than rhizomes because fossil fuels were assumed to heat glasshouses for raising seedling plugs (5.3 and 1.5 kg CO2 eq. C Mg (dry matter (DM))-1), respectively. Plastic mulch film reduced establishment time, improving crop economics. The breakeven yield was calculated to be 6 Mg DM ha-1 y-1, which is about half average UK yield for Mxg; with newer seeded hybrids reaching 16 Mg DM ha-1 in second year UK trials. These combined improvements will significantly increase crop profitability. The trade-offs between costs of production for the preparation of different feedstock formats show that bales are the best option for direct firing with the lowest transport costs (£0.04 Mg -1 km-1) and easy on-farm storage. However if pelleted fuel is required then chip harvesting is more economic. We show how current seed based propagation methods can increase the rate at which Miscanthus can be scaled up; x100 those of current rhizome propagation. These rapid ramp rates for biomass production are required to deliver a scalable and economic Miscanthus biomass fuel whose GHG emissions are 1/20th those of natural gas per unit of heat.